Analysis of Mini Pile Foundation in Istiqlal Mosque Loa Bakung Samarinda Construction Project Based on CPT and SPT Data - Liana, Ulwiyah Wahdah Mufassirin; Yatnikasari, Santi; Siregar, Adde Currie; Syahrul, Muhammad (JSE Journal of Science and Engineering, 2024)
Transportation as an activity of moving something from one place to another. The existence of various community activities causes the emergence of traffic movements. The more activities that take place, the more traffic generated. So that adequate infrastructure is needed to create a smooth movement. As the number of vehicles increases, the strength of the pavement decreases which results in road damage. Pavement in good condition in Samarinda City in 2020 decreased by around 6.3%, while roads in severely damaged conditions increased by almost 100% from 2015. Damage to pavement reduces the capacity of the previously planned roads. This affects the level of service on these roads, so it is necessary to compare the analysis of service levels with and without any damage. The research was conducted by surveying Ir. Sutami road, City of Samarinda with a length of 150 m. Primary data include the number of vehicles, road geometric data and documentation of road damage. The analytical method uses MKJI 1997. The volume of vehicles passing through Ir. Sutami as much as 1228.4 smp/hour on holidays and 3510.35 smp/hour on weekdays which are dominated by motorbikes. Road capacity Ir. Sutami in a condition without any damage, namely 6079.92 smp/hour which produces a V/C ratio of 0.58 with a service level of A, while currently the Ir. Sutami road with some damage such as holes and peeling so that the capacity decreased to 5251.067 smp/hour with a V/C ratio of 0.67.